Postmortem hemoglobin concentration changing in Sprague-Dawley white mouse - Beta Ahlam Gizela, Beta Ahlam Gizela (Universitas Gadjah Mada, 2001)
Background: Postmortem changes in a death body have a lot of purposes, one of them is predicting the time of death. The common method used to predict the time of death is by detecting hypostasis, rigidity, decreasing temperature, and decomposition.Objectives: To find out postmortem hemoglobin concentration changing pattern.Methods: This research is a preliminary study. We used Quasi Experimental Design. The subjects were 31 white male mice aged of two months old. The mouse blood was taken in a periodic time: antemortem, 0, 1, 2, and 3 hours postmortem, and hemoglobin concentration was examined using Sahli method.Results: Data taken from this research were analyzed by regression analysis and t-test. The result showed that postmortem hemoglobin against time pattern was a curve. The hemoglobin concentration is significantly decreased in the first hour (p<0.05), and then increased 2 hours later (p>0.05). There was no significant difference between antemortem and 0 hour postmortem (p>0.05). There was a significant difference between antemortem and 1, 2, and 3 hours postmortem (p<0.05).Conclusion: Postmortem hemoglobin concentration changing pattern is a curve, not linear. The hemoglo-bin concentration decreased in the first hour since death (statistically significant), then, increased in the second and third hour postmortem (statistically not significant). There is a significant difference between antemortem and 1, 2, and 3 hours postmortem.Keywords: Hemoglobin concentration -postmortem changes - time of death -blood